Community-acquired hyperkalemia in elderly patients: risk factors and clinical outcomes. (20th October 2016) - Turgutalp, Kenan; Bardak, Simge; Helvacı, Ilter; İşgüzar, Gizem; Payas, Ezgi; Demir, Serap; Kıykım, Ahmet
Abstract: Background: Although the risk and related factors of hyperkalemia developed in the hospital are known in elderly, risk and related factors of community-acquired hyperkalemia (CAH) in this population are not well known. This study was performed to investigate the risk of CAH in elderly and evaluate the related factors and clinical outcomes. Study design, setting and participants, intervention: Patients (aged ≥65 years) with hyperkalemia were screened. Group 1 (young-old); 65–74 years/old, Group 2 (middle-old); 75–84 years/old, Group 3 (oldest-old); ≥85 years/old, and Group 4 (control group); ≥65 years/old (normal serum potassium levels). The relation between CAH and hospital expenses (HE), the number of comorbid diseases (NCD), and all-cause of mortality rates (MR) were evaluated. We also investigated whether drugs, sex, and NCD are risk factors for the development of CAH. Results: There was a positive correlation between serum potassium levels and length of hospital stay, MR, HE, and NCD ( p <  0.001). Risk factors for CAH were the use of non-steroidal-anti inflammatory drugs (NSAIDs) (Odds Ratio [OR]: 2.679), spironolactone (OR: 2.530), and angiotensin converting enzyme inhibitors (ACEI) (OR: 2.242), angiotensin receptor blockers (ARB) (OR: 2.679), ≥2 comorbid diseases (OR: 2.221), female gender (OR: 2.112), and renal injury (OR: 5.55). CAH risk was found to be increased 30.03 times when any of ACEI, ARB, NSAIDs, or spironolactone is given to a patient with a renal injury. Conclusion: Use of NSAIDs, ACEI, ARB, spironolactone and increased NCD are all independent risk factors for CAH in the elderly, especially in patients with kidney diseases.